2020
DOI: 10.1111/1346-8138.15530
|View full text |Cite
|
Sign up to set email alerts
|

Diversity analysis of gut microbiota between healthy controls and those with atopic dermatitis in a Chinese population

Abstract: An increasing body of evidence suggests that gut microbiota is involved in atopic dermatitis (AD). We aimed to use high‐throughput sequencing to characterize the differences in the composition of the gut microbiota between healthy controls and patients with AD. Fecal samples from 93 volunteers were analyzed using 16S rRNA sequencing, including 44 patients with AD and 49 healthy control subjects, aged 6–22 years. Our data show that the operational taxonomic unit composition in patients with AD had greater compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…13 Depending on the studies, Bifidobacteria were either increased 13,18 or decreased 10,13,19 in AD patients. The same contradictory results were observed with Clostridia, 16,20,21 while Lactobacilli were mostly found decreased.- 13,18 Other studies reported that AD gut microbiome showed higher abundance of Clostridioides difficile, Escherichia coli and Staphylococcus aureus. 10 In this study, we used shotgun metagenomics to evaluate gut microbiota changes during BT, and how it is connected with the improvement of the pathology observed after BT (SCORAD).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…13 Depending on the studies, Bifidobacteria were either increased 13,18 or decreased 10,13,19 in AD patients. The same contradictory results were observed with Clostridia, 16,20,21 while Lactobacilli were mostly found decreased.- 13,18 Other studies reported that AD gut microbiome showed higher abundance of Clostridioides difficile, Escherichia coli and Staphylococcus aureus. 10 In this study, we used shotgun metagenomics to evaluate gut microbiota changes during BT, and how it is connected with the improvement of the pathology observed after BT (SCORAD).…”
Section: Introductionmentioning
confidence: 68%
“…10 In attempting to characterize the gut microbiota of patients with AD, observational studies, considering especially infants or children, used various techniques (mainly 16S rRNA sequencing, but also qPCR or cultivation) and reported sometimes-contradictory results. 13 Gut microbiota diversity was either decreased in patients with AD, [14][15][16] increased, 17 or without any difference. 13 Most studies focused mainly on Bifidobacteria, Clostridia and Lactobacilli.…”
Section: Introductionmentioning
confidence: 98%
“…Various studies demonstrated that AD is associated with gut dysbiosis, especially during early life (Table 2). AD patients display poor gut microbial diversity in several clinical trials [130][131][132][133][134][135][136][137][138], while contradictory results exist [139][140][141][142]. Similarly, to the skin, AD patients exhibit abundant S. aureus in their gut microbiota [143][144][145][146].…”
Section: The Gut Microbiota Profiles In Ad Patientsmentioning
confidence: 99%
“…Even though ten reports stated there were non-significant differences in the bacterial families between healthy and AD, [23][24][25][26][27][28][29][30][31][32] four articles support significant low abundance diversity in AD gut microbiome (Table 2). [33][34][35][36] The subjects of all the papers ranged from infants, toddlers, and children. Pregnant women as subjects were excluded from this review.…”
Section: Increase Decrease Referencesmentioning
confidence: 99%
“…However, their increased presence has been associated with food allergies and other atopic manifestations. 27,[35][36][37][38] Indeed, higher levels of Bacteroides in atopy could lead to the continuous production of lipopolysaccharides (LPS), the major component of the gram-negative cell wall, in the gut, which could trigger an inflammatory response. Moreover, Bacteroides species were reported to alter gut permeability.…”
Section: Atopic Dermatitismentioning
confidence: 99%